A comparison of the effects of traditional and wet mixing processes of rubber on metal friction and wear. Issue 31 (12th April 2021) - Han, Deshang; Zhang, Shoufeng; Wang, Kongshuo; Pan, Yi; Zhu, Donglin; Wang, Chuansheng; Pan, Yiren
Abstract: Prolonged operations of mixers cause wear of mixer rotors and chamber walls and affect the clearances between the rotors and chamber walls, which reduce the mixing effect, weaken the dispersion of the packing, and affect the quality of rubber products. In this study, the effects of traditional mixing and wet mixing on the friction and wear of the chamber, and the properties of rubber were compared by using 60 phr of a silica natural rubber formulation system. The results show that a silanization reaction occurs between silica and the silane coupling agent during the mixing process and that the reaction rate is fastest when the temperature of the mixing chamber is maintained between 145 and 155°C for 1 min during the mixing process. The products of silanization reaction are ethanol and water; the water vapor that forms at high temperatures corrodes the mixing chamber of the internal mixer and aggravates wear and tear. Due to the high dispersion of silica during wet mixing, the silanization reaction is more complete and water vapor is produced at a high temperature. Hence, the rubber compound obtained by wet mixing has more significant wear on the mixing chamber. Abstract : In this study, the effects of traditional mixing and wet mixing on the friction and wear of the chamber, and the properties of rubber were compared by using 60 phr of a silica natural rubber formulation system.